Study of the interactions between rosmarinic acid and bovine milk whey protein α-Lactalbumin, β-Lactoglobulin and Lactoferrin - Ferraro, Vincenza (2016)
Incorporation of polyphenols in dairy food is being considered as way to develop oral nutraceutical formulation due to their antioxidant and anti-inflammatory activities. However, polyphenols can interact with proteins, which gives rise to a significant loss of their biological properties. The objective of this research was to study the interactions of rosmarinic acid (RA) and bovine milk whey protein (i.e. α-Lactalbumin, β-Lactoglobulin and Lactoferrin). Radical quenching assay (ABTS), optical density, liquid chromatography (HPLC and FPLC), dynamic light scattering (DLS) and zeta-potential, Fourier transform infrared spectroscopy (FTIR), and differential scanning calorimetry (DSC) were used for the screening of the interactions at 0, 3, and 24 h of storage at 4 °C. Interactions were assessed both at neutral pH of the complexes inwater and acidic pH 3 and 4.5. Results show the occurrence of non-covalent interactions between RA and whey proteins, such as hydrophobic, hydrogen bonding, and dipole–dipole type. Radical quenching activity of RA decreased in the presence of milk proteins yet at the initial time especially in the case of α-Lactalbumin,meaning that the amount of free polyphenol diminished. Complex dimension was different depending on pH, and on primary and secondary structures of proteins. Interactions showed to be favored at the lowest pH, and reversible in all cases; nonetheless, complex RA–proteins were more stable than proteins alone.